2011
DOI: 10.1007/s11458-011-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic carbonates and dimethyl carbonate using CO2 as a building block catalyzed by MOF-5/KI and MOF-5/KI/K2CO3

Abstract: The synthesis of cyclic carbonates or dimethyl carbonate (DMC) using CO 2 as a building block is a very interesting topic. In this work, we found that the metalorganic framework-5 (MOF-5)/KI was an active and a selective catalytic system for the synthesis of cyclic carbonates from CO 2 and epoxides, and MOF-5/KI/ K 2 CO 3 was efficient for the preparation of DMC from CO 2 , propylene, and methanol by a sequential route. The impacts of temperature, pressure, and reaction time length on the reactions were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Han et al 27 reported that metal organic frameworks (MOFs) gave high conversions to cyclic carbonates when used as a cocatalyst. MOF-5 was investigated (comprised of Zn 4 O(BDC) 3 , where BDC is benzene-1,4-dicarboxylate).…”
Section: Alkali Metals (Sodium and Potassium)mentioning
confidence: 99%
“…Han et al 27 reported that metal organic frameworks (MOFs) gave high conversions to cyclic carbonates when used as a cocatalyst. MOF-5 was investigated (comprised of Zn 4 O(BDC) 3 , where BDC is benzene-1,4-dicarboxylate).…”
Section: Alkali Metals (Sodium and Potassium)mentioning
confidence: 99%
“…The synergistic effect of MOF‐5 and n ‐BuN 4 Br was believed to be the main reason for the high catalytic activity of the catalytic system under mild conditions. The same group reported MOF‐5/KI as an effective catalyst for the cycloaddition of CO 2 and propene oxide to produce propene carbonate …”
Section: Mofs: Structural Characteristics and Catalytic Performancementioning
confidence: 99%
“…46,47 However, in the case of MOF-5 grown around the fibers, the strong peaks around 1390 and 1600 cm –1 are assigned to the existence of organic linker, which is in the case of MOF-5 terephthalic acid. 48…”
Section: Resultsmentioning
confidence: 99%